The upper critical field and its anisotropy in (Li1−xFex)OHFe1−ySe. (14th November 2016) - Wang, Zhaosheng; Yuan, Jie; Wosnitza, J; Zhou, Huaxue; Huang, Yulong; Jin, Kui; Zhou, Fang; Dong, Xiaoli; Zhao, Zhongxian
Abstract: The temperature dependence of the upper critical field ( H c2 ) in a (Li1− x Fe x )OHFe1− y Se single crystal ( T c ≈ 40 K) has been determined by means of magnetotransport measurements down to 1.4 K both for inter-plane ( H ∥ c, H c 2 / / c ) and in-plane ( H ∥ a b, H c 2 / / a b ) field directions in static magnetic fields up to 14 T and pulsed magnetic fields up to 70 T. H c 2 / / c exhibits a quasilinear increase with decreasing temperature below the superconducting transition and can be described well by an effective two-band model with unbalanced diffusivity, while H c 2 / / a b shows a flattening below 35 K and follows the Werthamer–Helfand–Hohenberg (WHH) model incorporating orbital pair-breaking and spin-paramagnetic effects, yielding zero-temperature critical fields of H c 2 / / c ( 0 ) ≈ 67 T and H c 2 / / a b ( 0 ) ≈ 98 T. The anisotropy of the upper critical fields, γ ( T ) = H c 2 / / a b / H c 2 / / c monotonically decreases with decreasing temperature from about 7 near T c to 1.5 at 0 K. This reduced anisotropy, observed in most Fe-based superconductors, is caused by the Pauli limitation of H c 2 / / a b .